Indigenous Digital Technologies. The Taicho and Yelloknives Dene’s Web-Site and Cultural Online Archives - Armano, Linda (Rivista Italiana di Antropologia Applicata, 2019)
Cyberspace is only one of the many metaphors used to describe the Internet. While there is a growing body of literature on identity formation in cyberspace, there are important gaps in this field. One of these is related to the analysis of the use of digital technologies by the Northern Canadian Indigenous people. Precisely, the author, focusing her attention on Tåîchô and Yellowknives Dene communities in Northwest Territories of Canada analyzes the contents of their websites and online archives in order to understand how these native groups promote their culture and spread out their knowledge through digital technologies for working toward decolonization